Development and analysis of pulse detonation engine (PDE) with fuel-air premixed intake system - Nor Hassan, Abdul Hafiz (2015)
This research is on experimental studies of the pulse of detonation engine (PDE) at High Speed Reacting Flow Laboratory (HiREF) where the pulse detonation engine was equipped with a new design of a fuel-air premixed intake system. Pulse detonation engine is a power conversion device with simple mechanism and yet efficient. A premixed intake system is fabricated and assembled with a detonation tube with dimension of 50 mm inner diameter and 600 mm in length. Stoichiometric condition of fuel-air mixture for repetitive high-speed combustion is prepared for the pulse detonation engine with operating frequency system of 5Hz. Fuel and oxidizer are injected using gas injectors into air flow in intake system manifolds that connected to mixing chamber and detonation tube. The pressure produced in the tube is measured using pressure transducers located along the detonation tube. The pulse detonation engine model is evaluated with thermodynamics theory models; Ideal pulse detonation engine (PDE), Brayton cycle and Humphrey cycle. The thermodynamic cycle efficiency of the pulse detonation engine is analyzed and compared with non-premixed pulse detonation engine for evaluation. The simulation result indicated that ideal PDE operates at 0.24 thermal efficiency. The ideal pulse detonation engine is predicted to produce 276.3 N with generated impulse up to 68.5 s in stoichiometric condition of propane and air mixtures.